Annual bank and point bar morphodynamics of a meandering river determined by high‐accuracy multitemporal laser scanning and flow data. Issue 7 (7th July 2014) - Lotsari, E.; Vaaja, M.; Flener, C.; Kaartinen, H.; Kukko, A.; Kasvi, E.; Hyyppä, H.; Hyyppä, J.; Alho, P.
Abstract The knowledge has been insufficient concerning the effects of peak flows, and local bend and flow characteristics on annual morphodynamics of consecutive bends in meandering rivers. Therefore, it was determined how flow peak magnitude and duration affect morphodynamics, how the short‐term spatial evolution of a given meander bend associates with the neighboring bends, and how local bend and flow characteristics affect morphodynamics. The annual bank and point bar morphodynamics of eight consecutive bends of a subarctic meandering river were analyzed between 2009 and 2012 on the basis of high‐accuracy multitemporal data, measured by mobile and terrestrial laser scanning and an Acoustic Doppler Current Profiler. According to the results, multiple years of highly accurate data are crucial for a broader picture of meandering channel evolution. The results showed for the first time in detail that none of the years were similar in terms of point bar and bank morphodynamics. The duration of point bar submergence and maximum water stage was more important for evolution of the meandering channel than the local effects of each bend. The detailed topographical data of the present study confirmed that the higher the flow and water stage peak the more deposition occurred on point bars. More importantly, the independence of the short‐term spatial evolution of meander bends from the association with neighboring bends was confirmed. Erosion patterns did not relate particularly to the sinuosity or radius of curvature. A clear relation between velocity and bend curvature, on which some meander migration models rely, was not found.